Experiments on Fishing Net Preservation - Miyamoto, H; Shariff, A T (Indian Journal of Fisheries, 2016)
IT is common knowledge that fishing nets deteriorate either while in useor in storage. The weakening of fibres of the fishing nets is caused by physicalwear and tear, bacterial infection, action of organic matter like thefish slime, dead fish, etc., and temperature (Whiteleather, R. T. andBrown, H. H., 1945). All methods of preservation of fishing netsare meant to slow down the processes of deterioration. The Indianfishermen since ages are known to keep their fishing gears in goodcondition as long as possible, by treating them with some form of vegetablematter like the fruits, the nuts, the leaves and the barks of several trees.Though considerable progress has been made in other countries in the manufactureof net preservatives on a commercial scale and in the study of theiradvantageous application to diflferent types of fishing gears, no systematicwork has been done in India and other tropical countries, even on a studyof the vast resources of vegetable products in different forms available inlarge quantities and used in diflferent parts of the country, the methods ofpreservation adopted in each case, how far the nets become strengthenedby the application of these preservatives, the preserving qualities of eachpreservative, etc. Attempts have been made, therefore, in these series ofexperiments for a study of the above details and to observe how far theyÂ compare with the preservatives used in other parts of the world.